THERMODYNAMIC DESCRIPTION OF AQUEOUS NONELECTROLYTES AT INFINITE DILUTION OVER A WIDE RANGE OF STATE PARAMETERS - Akinfiev N.N.; Diamond L.W. (My University, 2003)
A new, virial-like equation of state (EoS) for describing the thermodynamic properties of aqueous nonelectrolytes at infinite dilution is proposed. It is based on the accurate EoS for a solvent (H2O) given by Hill (1990) and requires only three empirical parameters to be fitted to experimental data, and these are independent of temperature and pressure. Knowledge of the thermodynamic properties of a pure gas, together with these three parameters, enables prediction of the whole set thermodynamic properties of the solute at infinite dilution (chemical potential, entropy, molar volume, and apparent molar heat capacity) over a wide range of temperatures (0 to 500°C) and pressures (1 to 2000 bars), including the near-critical region. In the cases in which experimental thermodynamic data are lacking, the empirical parameters can be estimated solely from the known standard-state properties of the solute. The new EoS is compatible with the Helgeson-Kirkham-Flowers model for aqueous electrolytes, and thus it can be applied to reactions involving minerals, gases, and aqueous ions, in addition to uncharged species.